Short-time work, labor hoarding, and curtailed hiring: Establishment-level evidence from Japan - Chiu-Wei Kuo (Journal for Labour Market Research, 2024)
This study analyzes the mechanisms by which short-time work (STW) schemes affect firm's employment adjustments, using establishment-level data during the Great Recession from Japan. The findings show that STW leads to a decrease in both hiring and separations, with no significant positive effect on net employment. The observed curtailed hiring can be explained within the context of how STW promotes labor hoarding. STW encourages firms to maintain redundant employment by subsidizing the costs of labor hoarding. The excess labor surplus in firms adopting STW diminishes the incentive to recruit new workers in anticipation of the recovery period. Furthermore, as firms generally lack the motivation to hoard marginal workers, STW may exacerbate job security disparities between regular and marginal workers. These findings have important implications for policy evaluation, emphasizing the need for a comprehensive understanding of the potential adverse consequences of STW on labor market entrants and marginal workers.
Keywords: J23; J08; J63; 330; Labor hoarding; Scarring effect; Short-time work; The Great Recession